COMPARISON OF THE CLINICAL ACTIVITY OF TWO OXAZOLIDINONES – LINEZOLID AND TEDIZOLIDE: UNJUSTIFIED EXPECTATIONS - N. V. Dmitrieva; I. N. Petuhova; Z. V. Grigorievskaya; N. S. Bagirova; I. V. Tereshchenko (Сибирский онкологический журнал)
Skin and soft tissue infections are one of the most common nosocomial infections, which are caused most often by gram-positive bacteria (staphylococci, streptococci, enterococci) with multiple drug resistance. These infections are among the major nosocomial infections in oncology clinics along with respiratory and urinary tract infections, blood flow infections, febrile neutropenia, and fevers of unknown origin.The purpose of the study was to compare the clinical activity of two oxazolidinones: linezolid and tedizolide in patients with skin and soft tissue infections.Material and methods. We analyzed recent publications and data available in websites: rlsnet.ru, eucast.org, and medlux.ru.Results. Clinical trials showed that both oxazolidinones were comparable in clinical efficacy, microbiological activity, and incidence of side effects in skin and soft tissue infections caused by various resistant gram-positive microorganisms: methicillin-resistant staphylococcus aureus (MRSA) and vancomycin-resistant Streptococcus faecalis (VRE), as well as certain streptococci. The treatment regimen of tedizolide (200 mg once daily for 6 days) was compared with linezolid regimen (600 mg twice daily for 10 days). No comparisons were made with the 6-day linezolid regimen, although the authors concluded that shorter duration of treatment with tadizolide resulted in an equal effect. In addition, the minimum inhibitory concentrations (MICs) obtained by comparing the microbiological activity of these two agents showed the advantage of tedizolide against certain strains. However, the comparison was not made according to the EUCAST standards (Committee on Antimicrobial Susceptibility Testing). Concerning the cost of both drugs, treatment with linezolidom was 2-3 times cheaper than treatment with tidezolid, even with its shorter course.Conclusion. Thus, tedisolide was equally effective for linezolid. Data on the microbiological sensitivity of linezolid can be extrapolated to tedizolide in the absence of testing in laboratories. However, lower financial costs and wider range of microbiological activity make linezolid the drug of choice for the treatment of skin and soft tissue infections caused by resistant gram-positive microorganisms.